2012
DOI: 10.1371/journal.pone.0032520
|View full text |Cite
|
Sign up to set email alerts
|

Absence of RIP140 Reveals a Pathway Regulating glut4-Dependent Glucose Uptake in Oxidative Skeletal Muscle through UCP1-Mediated Activation of AMPK

Abstract: Skeletal muscle constitutes the major site of glucose uptake leading to increased removal of glucose from the circulation in response to insulin. Type 2 diabetes and obesity are often associated with insulin resistance that can be counteracted by exercise or the use of drugs increasing the relative proportion of oxidative fibers. RIP140 is a transcriptional coregulator with a central role in metabolic tissues and we tested the effect of modulating its level of expression on muscle glucose and lipid metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 62 publications
2
22
0
1
Order By: Relevance
“…of Pages 9 combustion of fat and a subsequent increase in energy status within the brown adipocytes. This conforms to a mechanism proposed by Fritah et al [74] in which increased mitochondrial uncoupling by UCP1 in muscle (in a model lacking a UCP1 transcriptional repressor) leads to an increased AMP/ATP ratio and subsequent AMPK activation. By contrast, b3-adrenergic stimulation increases AMPK phosphorylation in Ucp1 À/À adipocytes to the same extent as in WT adipocytes, indicating that AMPK activation is independent of the presence of UCP1 [54].…”
Section: Ampk Activation: Cause or Consequence Of Uncoupling In Bat?supporting
confidence: 91%
See 1 more Smart Citation
“…of Pages 9 combustion of fat and a subsequent increase in energy status within the brown adipocytes. This conforms to a mechanism proposed by Fritah et al [74] in which increased mitochondrial uncoupling by UCP1 in muscle (in a model lacking a UCP1 transcriptional repressor) leads to an increased AMP/ATP ratio and subsequent AMPK activation. By contrast, b3-adrenergic stimulation increases AMPK phosphorylation in Ucp1 À/À adipocytes to the same extent as in WT adipocytes, indicating that AMPK activation is independent of the presence of UCP1 [54].…”
Section: Ampk Activation: Cause or Consequence Of Uncoupling In Bat?supporting
confidence: 91%
“…By contrast, b3-adrenergic stimulation increases AMPK phosphorylation in Ucp1 À/À adipocytes to the same extent as in WT adipocytes, indicating that AMPK activation is independent of the presence of UCP1 [54]. The consequential mechanism proposed by Fritah et al [74] is challenged by these data, emphasising that future research is necessary to provide clarity on whether AMPK activation is a cause or a consequence of uncoupling in BAT.…”
Section: Ampk Activation: Cause or Consequence Of Uncoupling In Bat?mentioning
confidence: 89%
“…Several reports have shown that the skeletal muscle fiber composition is an important determinant in metabolism. Moreover, it is well established that slow twitch type I fibers act in glucose and lipid metabolism and endurance training promotes an increase of type I fiber muscles (67)(68)(69)(70)(71)(72). Indeed, the KO mice ran less than WT mice in the low intensity running regime until exhaustion.…”
Section: Ms Spectramentioning
confidence: 99%
“…The expression and promoter activity of CIDEA, an important regulatory factor in adipose cell function and obesity, is repressed by NRIP1 and induced by PGC-1α [100]. These genes are also involved in glucose uptake by affecting the regulation of both transcription and subcellular localization of the insulin-sensitive glucose transporter GLUT4 [101]. This evidence suggested that NRIP1 might be a potential therapeutic target in the treatment of insulin resistance in obese and type 2 diabetic patients [101].…”
Section: Type 2 Diabetes and Obesitymentioning
confidence: 99%
“…These genes are also involved in glucose uptake by affecting the regulation of both transcription and subcellular localization of the insulin-sensitive glucose transporter GLUT4 [101]. This evidence suggested that NRIP1 might be a potential therapeutic target in the treatment of insulin resistance in obese and type 2 diabetic patients [101]. Accordingly, mice lacking Nrip1 are lean, show resistance to high-fat diet-induced obesity and have increased oxygen consumption [102].…”
Section: Type 2 Diabetes and Obesitymentioning
confidence: 99%